Comparison of the impact of the learning system during the COVID-19 Pandemic in several countries and Indonesia - Muji, Anggarda Paramita; Falma, Fris Okta; Rusdinal, Rusdinal; Ananda, Azwar; Gistituati, Nurhizrah; Hidayat, Hendra (Universitas Negeri Padang, 2022)
Online learning is an alternative during the COVID-19 pandemic. This study aims to empirically verify the impact of the learning system during the COVID-19 pandemic in several countries and Indonesia. The method used in writing this article is using the prism method, which is part of the literature search method from national and international article sources, which is carried out using an indexed search on Google Scholar. The articles reviewed were the latest 49 articles from 2020 to 2022, consisting of 40 national journals and 9 international journals. The results of the study are presented as follows; (1) The search results prove an increase in the number of articles published from 2020-2021; (2) The distribution of articles by type and method of data is presented using more qualitative data; (3) The results showed that the impact of the learning system during the covid-19 pandemic had a major impact on the learning system, namely the positive and negative impacts of online learning carried out by every school facing the covid-19 pandemic. Online learning itself is very influential on learning during the pandemic and is the most widely used. Digital literacy competence is highly demanded in the conditions of the COVID-19 pandemic.